Method for manufacturing dry type carbon dioxide adsorbing molding for small and medium-sized ships
Patent Information
- Application Number
- KR1020230163182
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-11-23
- Filing Date
- 2023-11-22
- Publication Date
- 2026-10-21
- Estimated Expiration
- 2043-11-22
Smart Images

Figure 112023130351596-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for manufacturing a dry carbon dioxide adsorption molded body, and more specifically, to a method for manufacturing a dry carbon dioxide adsorption molded body for small and medium-sized vessels having low pressure loss and a high adsorption rate. Background Technology
[0002] As we enter the era of carbon neutrality and regulations on ship exhaust gases have recently become stricter, the need for technology capable of reducing greenhouse gases (especially CO2) in ship exhaust is emerging. However, existing exhaust gas reduction devices focus on reducing SOx, NOx, or fine dust, and the only reduction devices for greenhouse gases are wet-type devices installed for large vessels.
[0003] However, given that small and medium-sized vessels constitute a much larger number of coastal areas, greenhouse gas reduction systems for these vessels are essential to effectively prevent air pollution caused by their exhaust. Yet, since development has been limited to large vessels, the equipment itself is prohibitively expensive. Furthermore, greenhouse gas reduction devices designed for large vessels cannot be installed on small and medium-sized ships due to weight and volume constraints. Consequently, there is currently a complete lack of greenhouse gas reduction technologies applicable to small and medium-sized vessels. Therefore, there is a pressing need to develop small, lightweight adsorbents suitable for greenhouse gas adsorption systems for small and medium-sized ships.
[0004] Meanwhile, in the case of conventional dry carbon dioxide adsorbents used for other purposes, a method is mainly used in which a powder-form adsorbent flows along the fluidized bed to adsorb carbon dioxide without a separate molding process. However, since exhaust gas reduction devices for small and medium-sized vessels must reduce carbon dioxide in a one-pass manner, using a powder-form carbon dioxide adsorbent results in excessive pressure loss and significant energy loss for fluid flow, making it difficult to expect a high adsorption rate. The problem to be solved
[0005] The problem that the present invention aims to solve is to provide a method for manufacturing a dry carbon dioxide adsorption molded body that is applicable to greenhouse gas reduction devices of small and medium-sized vessels using a one-pass type, has low pressure loss, and has a high adsorption rate.
[0006] Another problem that the present invention aims to solve is to provide a dry carbon dioxide adsorption molded body manufactured by the above method.
[0007] The problems that the present invention aims to solve are not limited to those mentioned above, and other unmentioned problems will be clearly understood by those skilled in the art to which the present invention belongs from the description below. means of solving the problem
[0008] A method for manufacturing a dry carbon dioxide adsorption molded body according to one embodiment of the present invention for achieving the above objective comprises the steps of: preparing a mixture by adding and mixing a solvent, an amine compound, a silicon compound, a support raw material, and a structural guide forming the framework of the support into a reaction vessel; forming adsorbent unit particles by adding a binder that binds the support raw material to the mixture and drying at a predetermined temperature; crushing the adsorbent unit particles so that the size of the adsorbent unit particles becomes uniform; and manufacturing a solid molded body by extrusion molding the adsorbent unit particles.
[0009] The above solvent may be one or more selected from the group consisting of water, methanol, ethanol, methyl chloride, carbon tetrachloride, and tetrahydrofuran.
[0010] The above amine compound may be one or more selected from the group consisting of ethylenediamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, hexaethyleneheptamine, polyethyleneimine, and polypropyleneimine.
[0011] The above silicon compound may be sodium silicate.
[0012] The above support material may be one or more selected from the group consisting of bentonite, attapulgite, kaolinite, montmorillonite, ball clay, fullerto, hectorite, palygorskite, saponite, sepiolite, halloysite, silica, calcium sulfate, zeolite, synthetic zeolite, alumina, fumed silica, activated carbon, and metal-organic frameworks.
[0013] The above structural derivative may be one or more selected from the group consisting of tetramethylammonium phosphate (TMAH2PO4), tetraethylammonium phosphate (TEAH2PO4), tetrapropylammonium phosphate (TPAH2PO4) and tetrabutylammonium phosphate (TBAH2PO4).
[0014] The above mixture may consist of 10 to 20 weight% of the amine compound, 1 to 3 weight% of the silicon compound, 10 to 20 weight% of the support raw material, 1 to 3 weight% of the structure derivative, and the remainder being the solvent.
[0015] The above binder may be methyl cellulose.
[0016] The above binder may be added in an amount of 30 to 50 parts by weight based on 100 parts by weight of the mixture.
[0017] The above adsorbent unit particles may be silica adsorbents in which polyethyleneimine modified by partial substitution with epoxybutane is supported on fumed silica.
[0018] After adding the binder to the mixture, it can be dried at 120 to 140 degrees to prevent oxidation of the amine compound.
[0019] The above solid molded body may be in the shape of a polyhedron, a polygonal prism, or a cylinder.
[0020] The above mixture may consist of 15% by weight of the amine compound, 1.5% by weight of the silicon compound, 15% by weight of the support raw material, 1.8% by weight of the structure derivative, and the remainder being the solvent.
[0021] The above-mentioned solid molded body can be manufactured by one-pot synthesis, in which the final compound is synthesized by continuously adding reactants in a single reaction vessel without separately purifying the intermediate product.
[0022] The above-mentioned solid molded body can be used in a greenhouse gas reduction device for small and medium-sized vessels that reduces carbon dioxide in a one-pass manner.
[0023] A dry carbon dioxide adsorption molded body according to one embodiment of the present invention for achieving the above other objectives is manufactured according to the previously mentioned method.
[0024] Specific details of other embodiments are included in the specific contents and drawings. Effects of the invention
[0025] As described above, according to the method for manufacturing a dry carbon dioxide adsorption molded body and the dry carbon dioxide adsorption molded body manufactured thereby, the invention manufactures an adsorption molded body by simultaneously adding a support material, an amine compound, etc., into a single reaction vessel without separately performing the molding process of the adsorbent unit particles and the loading process of the amine compound, followed by mixing, drying, grinding, and molding steps. As such, since the present invention follows one-pot synthesis, the process itself is simple and the process time is shortened, making large-scale manufacturing possible.
[0026] In addition, when the experimental group according to the present invention was compared with the control group (where the adsorbent unit particles, molding process, and amine compound loading process were performed separately), it was observed that the size of the adsorbent unit particles was similar, but the BET specific surface area increased and the total pore volume increased by more than 60%. In addition, TGA analysis confirmed that the carbon dioxide adsorption capacity was also superior. Brief explanation of the drawing
[0027] FIG. 1 is a flowchart illustrating a method for manufacturing a dry carbon dioxide adsorption molded body according to one embodiment of the present invention. Figure 2 is a graph showing the results of a nitrogen isotherm adsorption experiment based on BET analysis. Figure 3 is an SEM image showing adsorbent unit particles constituting a solid molded body. Figure 4 is a graph showing the carbon dioxide adsorption capacity measured by thermogravimetric analysis. Specific details for implementing the invention
[0028] The advantages and features of the present invention and the methods for achieving them will become clear by referring to the embodiments described below in detail together with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed below but may be implemented in various different forms. These embodiments are provided merely to ensure that the disclosure of the present invention is complete and to fully inform those skilled in the art of the scope of the invention, and the present invention is defined only by the scope of the claims. Throughout the specification, the same reference numerals refer to the same components.
[0029] The present invention manufactures a dry carbon dioxide adsorption molded body according to one-pot synthesis. Here, "one-pot synthesis" refers to a method of synthesizing a final compound through multiple reaction processes by continuously adding reactants in a single reaction vessel without separately purifying intermediate products.
[0031] A method for manufacturing a dry carbon dioxide adsorption molded body according to an embodiment of the present invention will be described in detail below with reference to the attached drawings. FIG. 1 is a flowchart illustrating a method for manufacturing a dry carbon dioxide adsorption molded body according to an embodiment of the present invention.
[0032] First, a solvent, an amine compound, a silicon compound, a support material, and a structure derivative are added to a reaction vessel and mixed to prepare a mixture (S10). In this embodiment, the mixture was stirred at room temperature for 2 hours.
[0033] The solvent may consist of one or more selected from the group consisting of water, methanol, ethanol, methyl chloride, carbon tetrachloride, and tetrahydrofuran. Preferably, the solvent may consist of water.
[0034] The amine compound may consist of one or more selected from the group consisting of ethylenediamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, hexaethyleneheptamine, polyethyleneimine, and polypropyleneimine. Preferably, the amine compound may consist of polyethyleneimine. More preferably, the amine compound may be polyethyleneimine (EB-PEI) modified by partial substitution with epoxybutane.
[0035] Silicon compounds serve to bind the support material and can be composed of sodium silicate. Silicon compounds serve to increase the strength of the adsorbent unit particles and the solid molded body.
[0036] The support material may consist of one or more selected from the group consisting of bentonite, attapulgite, kaolinite, montmorillonite, ball clay, fullerto, hectorite, palygorskite, saponite, sepiolite, halloysite, silica, calcium sulfate, zeolite, synthetic zeolite, alumina, fumed silica, activated carbon, and metal-organic frameworks. Preferably, the support material may consist of fumed silica. Fumed silica is a synthetic silica produced by a dry method, is a high-purity material of 99.9% or higher, and can be produced by gas-phase pyrolysis of a chlorosilane compound.
[0037] A structural derivative is a compound that forms the framework of a support and serves as a template for forming a specific structure. The structural derivative may consist of one or more selected from the group consisting of tetramethylammonium phosphate (TMAH2PO4), tetraethylammonium phosphate (TEAH2PO4), tetrapropylammonium phosphate (TPAH2PO4), and tetrabutylammonium phosphate (TBAH2PO4). Preferably, the structural derivative may consist of tetraethylammonium phosphate.
[0038] The above mixture may consist of 10 to 20 weight% of an amine compound, 1 to 3 weight% of a silicon compound, 10 to 20 weight% of a support raw material, 1 to 3 weight% of a structure derivative, and the remainder being a solvent. Preferably, the above mixture may consist of 15 weight% of an amine compound, 1.5 weight% of a silicon compound, 15 weight% of a support raw material, 1.8 weight% of a structure derivative, and the remainder being a solvent.
[0039] A binder is added to the mixture prepared in this way and dried at a predetermined temperature to form adsorbent unit particles (S20). In this embodiment, after adding the binder to the mixture, the solvent was removed by drying at 120 to 140 degrees, preferably 130 degrees, for 24 to 32 hours so that oxidation of the amine compound did not occur.
[0040] The binder is an organic binder that binds the support material and may consist of methyl cellulose. The binder may be added in an amount of 30 to 50 parts by weight based on 100 parts by weight of the mixture. Preferably, the binder may be added in an amount of 40 parts by weight based on 100 parts by weight of the mixture.
[0041] The adsorbent unit particles may be in the form of powder. Specifically, the adsorbent unit particles may be a silica adsorbent in which polyethyleneimine modified by partial substitution with epoxybutane is supported on fumed silica.
[0042] Next, the adsorbent unit particles are placed in a grinder and ground so that the size of the adsorbent unit particles becomes uniform after drying (S30). In this embodiment, the adsorbent unit particles were placed in a grinder and ground at room temperature for 1 hour.
[0043] Next, the adsorbent unit particles are extruded to produce a solid molded body (S40). The solid molded body may be formed in the shape of a polyhedron, a polygonal prism, or a cylinder.
[0044] As described above, a dry carbon dioxide adsorption molded body can be manufactured through the mixing step, drying step, grinding step, and molding step.
[0046] The performance evaluation of the experimental example and the comparative example of the present invention will be compared below with reference to FIGS. 2 to 4. FIG. 2 is a graph showing the results of a nitrogen isothermal adsorption experiment according to BET analysis. FIG. 3 is an SEM image showing adsorbent unit particles constituting a solid molded body. FIG. 4 is a graph showing the carbon dioxide adsorption capacity measured by thermogravimetric analysis.
[0047] In this experimental example, 66.7 wt% water, 15 wt% polyethyleneimine (EB-PEI) partially modified with epoxybutane, 1.5 wt% sodium silicate, 15 wt% fumed silica, and 1.8 wt% tetraethylammonium phosphate (TEAH2PO4) were added to a reaction vessel and stirred at room temperature for 2 hours. A binder composed of methyl cellulose was added to this mixture, and then dried at 130°C for 24 hours to produce adsorbent unit particles in powder form. The binder was added at a ratio of 40 parts by weight based on 100 parts by weight of the mixture. The adsorbent unit particles consist of a silica adsorbent in which polyethyleneimine partially modified with epoxybutane is supported on fumed silica. Subsequently, the dried adsorbent unit particles were placed in a grinder and ground at room temperature for 1 hour. The crushed adsorbent unit particles were extruded at high temperature to complete the solid molded body.
[0048] In the comparative example, water, fumed silica, and sodium silicate were placed in a reaction vessel, mixed, and then dried to produce a support in powder form. In a process separate from the production of the support, tetraethylammonium phosphate was added to EB-PEI and coated onto the surface of the support to produce adsorbent unit particles. These adsorbent unit particles were extruded to complete a solid molded body.
[0049] As shown in Fig. 2, nitrogen adsorption / desorption curves were measured for the solid molded bodies prepared by the experimental example and the comparative example. In the case of total pore volume, the experimental example (0.029 cm²) 3 / g) is a comparative example (0.018 cm 3 It was confirmed to be 28% improved compared to / g).
[0050] As seen in the SEM image of the solid molded body surface taken with a scanning electron microscope at 100,000x magnification in Fig. 3, the adsorbent unit particles (powder) of the experimental example have a powder size substantially similar to that of the comparative example, but as observed in Fig. 2, the porosity of the example was confirmed to be higher than that of the comparative example.
[0051] As shown in Fig. 4, the adsorption capacity of the experimental example and the comparative example was analyzed using a thermogravimetric analysis (TGA). For CO2 adsorption, the solid molded body was placed in a TGA pan, and the adsorption capacity was measured by flowing 15% CO2 and 85% N2 at 45 sccm while maintaining the temperature at 60°C for 20 minutes. Subsequently, for CO2 desorption, 100% CO2 was flowed at 45 sccm while maintaining the temperature at 110°C for 20 minutes. In the case of carbon dioxide adsorption capacity, it was confirmed that the experimental example (2.22 mmol / g) was improved by more than 30% compared to the comparative example (1.69 mmol / g). In addition, regarding the CO2 working capacity, it was confirmed that the experimental example (1.80 mmol / g) was improved by 9% compared to the comparative example (1.65 mmol / g).
[0053] Although embodiments of the present invention have been described above with reference to the attached drawings, those skilled in the art will understand that the present invention may be implemented in other specific forms without changing its technical concept or essential features. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive.
Claims
Claim 1 A method for manufacturing a dry carbon dioxide adsorption molded body for small and medium-sized vessels, comprising the steps of: preparing a mixture by adding and mixing a solvent, a support raw material composed of an amine compound, a silicon compound, and fumed silica, and a structural guide forming the framework of the support, into a reaction vessel; forming adsorbent unit particles by adding a binder that binds the support raw material to the mixture and drying at a predetermined temperature; crushing the adsorbent unit particles so that the size of the adsorbent unit particles becomes uniform; and manufacturing a solid molded body by extrusion molding the adsorbent unit particles, wherein the solvent is a polar solvent composed of one or more selected from the group consisting of water, methanol, ethanol, methyl chloride, and tetrahydrofuran. Claim 2 A method for manufacturing a dry carbon dioxide adsorption molded body according to claim 1, characterized in that the mixture comprises 15% by weight of the amine compound, 1.5% by weight of the silicon compound, 15% by weight of the support raw material, 1.8% by weight of the structure derivative, and the remainder being the solvent. Claim 3 A method for manufacturing a dry carbon dioxide adsorption molded body according to claim 1, wherein the amine compound is one or more selected from the group consisting of ethylenediamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, hexaethyleneheptamine, polyethyleneimine, and polypropyleneimine. Claim 4 A method for manufacturing a dry carbon dioxide adsorption molded body according to claim 1, characterized in that the silicon compound is sodium silicate. Claim 5 A method for manufacturing a dry carbon dioxide adsorption molded body according to claim 1, characterized in that the solid molded body is manufactured by one-pot synthesis in which reactants are continuously added in a single reaction vessel to synthesize the final compound without separately purifying the intermediate product. Claim 6 A method for manufacturing a dry carbon dioxide adsorption molded body according to claim 1, wherein the structural derivative is one or more selected from the group consisting of tetramethylammonium phosphate (TMAH2PO4), tetraethylammonium phosphate (TEAH2PO4), tetrapropylammonium phosphate (TPAH2PO4), and tetrabutylammonium phosphate (TBAH2PO4). Claim 7 A method for manufacturing a dry carbon dioxide adsorption molded body according to claim 1, wherein the mixture comprises 10 to 20 weight% of the amine compound, 1 to 3 weight% of the silicon compound, 10 to 20 weight% of the support raw material, 1 to 3 weight% of the structure derivative, and the remainder being the solvent. Claim 8 A method for manufacturing a dry carbon dioxide adsorption molded body according to claim 1, characterized in that the binder is methyl cellulose. Claim 9 A method for manufacturing a dry carbon dioxide adsorption molded body according to claim 1, characterized in that the binder is added in an amount of 30 to 50 parts by weight based on 100 parts by weight of the mixture. Claim 10 A method for manufacturing a dry carbon dioxide adsorption molded body according to claim 1, characterized in that the adsorbent unit particles are silica adsorbents in which polyethyleneimine modified by partial substitution with epoxybutane is supported on fumed silica. Claim 11 A method for manufacturing a dry carbon dioxide adsorption molded body according to claim 1, characterized by adding the binder to the mixture and then drying at 120 to 140 degrees so as not to cause oxidation of the amine compound. Claim 12 A method for manufacturing a dry carbon dioxide adsorption molded body according to claim 1, characterized in that the solid molded body is in the shape of a polyhedron, a polygonal prism, or a cylinder. Claim 13 A dry carbon dioxide adsorption molded body manufactured according to any one of paragraphs 1 to 12.
Citation Information
Patent Citations
Amine-based carbon dioxide adsorbent including alkylammonium phosphate based chelating agent and Method for preparing the same
KR1020220120278A
Method for preparing spherical amine-based carbon dioxide adsorbent by one-pot synthesis
KR1020220120279A
Composition for preparing acidic gas adsorbent, acidic gas adsorbent and method of preparing acidic gas adsorbent
KR102380516B1
Method for manufacturing synthetic zeolite using spent catalyst generated in petrochemical process and adsorbent manufactured thereby
KR102393723B1